Регион как единица стабильности в (гео)политике XXI века - Zadorożniuk, Ella (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2003)
Internal identity of a region is a factor that promotes political stability. Western Europe is a particular example here. The significance of regions, which is clearly emphasised in Europe, may become a prerequisite for their mutual assimilation. This causes numerous problems but also contributes to increased interdependence between nations and regions. The potential of regional identity may be treated as a factor that reduces the consequences of the revival of national or nationalistic tendencies on the one hand, and those of intensified globalisation on the other. A decade of contradictory experience in the formation of regional identity in Central Europe confirms this hypothesis. The emergence of clear regional structures as well the reinforcement of a new regiona identity of Central European countries in politics and then in economics may diminish the level of various hazards ranging from political ones to environmental.

Tożsamość wewnątrzregionalna jest czynnikiem sprzyjającym stabilności. Szczególnie znaczący jest tutaj przykład Europy Zachodniej. Wyraźnie zarysowana pozycja regionów w Europie może słuzyć jako przesłanka do ich wzajemnego upodabniania się, co powoduje wiele problemów, ale zarazem zwiększa współzależność nie tylko między państwami, ale i między regionami. W takim przypadku procesy globalizacji nie muszą mieć charakteru „bezadresowgo”. Potencjał regionalnej tożsamości można traktować jako fenomen, który redukuje skutki odrodzenia narodowych i nacjonalistycznych tendencji z jednej strony oraz intensyfikacji globalizacji – z drugiej. Dziesięcioletnie i skrajnie sprzeczne doświadczenia formowania regionalnych tożsamości w Centralnej Europie potwierdzaj¹ s³usznoœæ tej hipotezy. Krystalizacja regionalnych struktur i umocnienie nowej regionalnej identycznoœci pañstw Europy Centralnej – najpierw w polityce, a potem i w ekonomii – mo¿e obni¿yæ poziom ró¿norakich nie - bezpieczeñstw, zaczynaj¹c od politycznych, a koñcz¹c na ekologicznych.
A Region as a Stability Unit in Geopolitics of 21.tCentury